Clinical and Non-Clinical Predictors of Length of Stay in Indonesian hospitalized COPD (Chronic Obstructive Pulmonary Disease) Patients: Prediktor Klinik dan Non-Klinik Lama Rawat Inap Pasien PPOK (Penyakit Paru Obstruktif Kronis) di Rumah Sakit - Matra Novalia Palipadang; Marianti A. Manggau; Muh. Akbar Bahar (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2022)
Background: COPD (chronic obstructive pulmonary disease) is a chronic disease characterized by persistent airflow limitation and is a major cause of morbidity and mortality. Objectives: This study aimed to analyze potential predictors of length of hospitalization (length of stay/ LOS) of COPD patients in the Anutapura Hospital, Central Sulawesi Province, Indonesia. Material and Methods: This study is an analytical descriptive using a cross-sectional design. The data were collected from medical records of COPD patients at Anutapura Hospital, Central Sulawesi Province, during 2018-2021. Information about demographic data (age, gender, weight), clinical data (comorbidities, single/combination antibiotics, route of antibiotic administration, type of antibiotics, oxygen therapy, history of hospital admission due to pneumonia, with/without exacerbations), and non-clinical data (type of insurance and treatment class) were extracted. Multivariate linear regression was used to identify the predictors of LOS. Results: A total of 210 COPD patients were identified. The results of univariate analysis showed that there were several potential predictors of LOS in COPD patients (p < 0.25), namely: age (B: 0.03, 95% CI: 0.01-0.05), treatment class (B: 1.16, 95% CI: 0.01-2.33), exacerbation (B: 0.55, 95% CI: -0.24-1.35), comorbidities (B: 0.68, 95% CI: 0.25-1.12), and single/combination antibiotics (B: 1.43, 95% CI: 0.33- 2.54). The results of the multivariate analysis indicated that the older (B: 0.03, 95% CI: 0.01-0.06, p = 0.02) COPD patients and the more comorbidities (B: 0.54, 95% CI: 0.07-1.00, p = 0.02) that they had, the longer the LOS that they experienced. Conclusions: In this study, age and patient comorbidities are independent predictors of LOS in COPD patients in the Anutapura Hospital, Central Sulawesi Province, Indonesia.